P514Externalised pacemakers are valuable in treatment of brady as well as tachyarrhythmias - a single tertiary non device extraction cardiac center experience. (18th June 2020) - Panchal, G; Ahmad, S; Spencer, C; Barr, C; Arya, A; Petkar, S
Abstract: Introduction: Temporary transvenous pacing (TPW) is a very useful procedure to control symptoms and/or correct significant hemodynamic compromise secondary to acute bradycardia as well as ventricular arrhythmias. It can be associated with significant complications (14-40%) e.g., loss of capture, displacement, infection, perforation, venous thrombosis, pulmonary embolism, or rarely, even death. The 2018 ACC/AHA/HRS guidelines on the management of bradycardia give a Class IIa indication for externalised pacemakers (ExPPM) in patients requiring prolonged TPW support while the 2015 ESC guidelines on ventricular arrhythmias and sudden cardiac death give a Class IIa indication for overdrive pacing in the setting of acute coronary syndromes. However,  published evidence for the former indication is modest (Level of evidence: B-NR) and lacking for the latter (Level of evidence: C).  Aim: To describe the experience of use of ExPPM in a high volume single tertiary non device extraction cardiac center over 45 months.  Methods:   Retrospective study of medical records from January 2016 - September 2019.   Results:  N = 34 during which the centre undertook 1341 new simple and complex device implants. Mean age: 73 ± 12 years, 20/34 (58.8%) males. Indication: symptomatic sinus node disease: 7/34 (20.6%),  AV node disease: 23/34 (67.6%%), overdrive pacing for ventricular arrhythmias: 4/34 (11.8%) - late monomorphic VT secondary ST elevation myocardial infarction 2/4, polymorphic VT secondary to methadone toxicity 1/4, ventricular fibrillation secondary to bradyarrhythmia 1/4. Majority (27/34, 79.4%) had an ExPPM  because of sepsis (pneumonia 12/27; unknown focus 3/27,  TPW site infection 2/27, biliary sepsis, necrotising fasciitis, urinary tract infection, sternal wound infection, endocarditis, thrombophlebitis 1 each. Mean duration of implantation: 13.9 ± 11 days. Right internal jugular vein was the most common site (22/34, 64.7%) for introduction of the active fixation lead. Type of ExPPM: single chamber (VVI): 32/34 (94.1%), dual chamber (DDD): 2/34 (5.9%). 13/15 (38.2%) underwent permanent pacemaker implantation and 2/15 (13.3%) cardiac resynchronisation therapy - defibrillator following an ExPPM. Complications: 1/34 (2.9%) bleeding from the puncture site requiring transfusion. Six patients died during the course with deterioration in co-existing medical condition. Conclusion: In our experience, ExPPM are not only a very useful intervention in patients who require prolonged support for bradyarrhythmias but can also be used to stabilise patients with recurrent tachyarrhythmias who need overdrive suppression, buying vital time before proceeding to definite therapy. They are associated with a low complication rate. We recommend that centers should have a low threshold for implanting such devices at the outset, in preference to TPW, in those patients where prolonged stabilisation of the heart rhythm is anticipated.